2019
DOI: 10.1108/acmm-07-2018-1976
|View full text |Cite
|
Sign up to set email alerts
|

Modelling input data interactions for the optimization of artificial neural networks used in the prediction of pitting corrosion

Abstract: Purpose This paper aims to predict the localized corrosion resistance by the application of artificial neural networks. It emphasizes the importance to take into account the relationships between the physical parameters before presenting them to the network. Design/methodology/approach The work was conducted in two phases. At the beginning, the authors executed an experimental program to measure pitting corrosion resistance of carbon steel in an aqueous environment. More than 900 electrochemical experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The properties of the chemical solutions are close to that of the cooling fluid used in the circuit. Design/methodology/approach -In a previous study, this paper demonstrated the effectiveness of machine learning in predicting the localized corrosion resistance of a material by considering as input data the physicochemical properties of its environment (Boucherit et al, 2019). With the present study, the authors improve the results by considering as input data, cathodic currents.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The properties of the chemical solutions are close to that of the cooling fluid used in the circuit. Design/methodology/approach -In a previous study, this paper demonstrated the effectiveness of machine learning in predicting the localized corrosion resistance of a material by considering as input data the physicochemical properties of its environment (Boucherit et al, 2019). With the present study, the authors improve the results by considering as input data, cathodic currents.…”
mentioning
confidence: 78%
“…The cathodic current values are the input data. The present work differs from that carried out previously where we considered as input data the physicochemical properties of the solution (Boucherit et al, 2019). In the present work, we limit observations only to the current response of the material following a cathodic potential scan and then speculate on its resistance to pitting corrosion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrary, it is difficult or even impossible to predict outcome with conventional statistical models [7]. The major advantages of using artificial intelligence is that it does not need the explicit knowledge behavior of phenomena and any kind of mathematical equation in advance [8]. The intelligent models need only to be trained by sufficient data under optimal parameters [9] to predict the target with high performance [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, various models such as Deep Networks using Auto-Encoder (DN-AE), Artificial Neural Network (ANN), Artificial Neural Network combined with Particle Swarm Optimization algorithm (PSO-ANN) and Ant Colony Optimization (ACO) combined with Artificial Neural Network (ACO-ANN) are used to predict the mass loss of cement raw materials due to decarbonation process. These algorithms are intelligent methodologies that have shown successful and promising results in the domains of modelling and prediction [8] and can be useful and powerful alternative [9]. DN-AE has achieved a good prediction performance on limited protein phosphorylation [10].…”
Section: Introductionmentioning
confidence: 99%